Single or Blended Application of Non-Microbial Plant-Based Biostimulants and Trichoderma atroviride as a New Strategy to Enhance Greenhouse Cherry Tomato Performance - Lorena Vultaggio; Michele Ciriello; Emanuela Campana; Pietro Bellitto; Beppe Benedetto Consentino; Youssef Rouphael; Giuseppe Colla; Fabiana Mancuso; Salvatore La Bella; Simona Napoli; Leo Sabatino (Plants)
The need to increase yield and enhance the sustainability of crop production systems has led to the development and employment of natural products, such as plant biostimulants. In recent years, a number of reports have researched the effects of biostimulants on plant performance; however, few studies have focused on the mutual application of microbial and/or non-microbial biostimulants. This research, conducted in the framework of the SO.MI.PR.O.N regional project, aimed to investigate the single or mutual application of three biostimulants, a tropical plant extract (PE), a vegetal protein hydrolysate (PH), and Trichoderma atroviride, on ‘Creativo’ F1 cherry tomato plants cultivated during two growing cycles (2022–2023 and 2023–2024). Our results showed that plants treated with the combination Tricho + PE + PH had statistically significant higher fresh shoot biomass (+64.2%, 1647.0 g plant−1), total fruit production (+37.9%, 1902.5 g plant−1), marketable fruit production (+52.9%, 1778.5 g plant−1), and average weight of marketable fruits (+53.1%, 17.0 g) compared to control plants (untreated plants). Furthermore, biostimulant treatments, especially T. atroviride, variably enhanced cherry tomato fruits’ qualitative traits, such as firmness, total soluble solids, ascorbic acid, lycopene, and total polyphenols compared to control plants. Overall, the best combinations to increase tomato fruit qualitative features were PE + PH, Tricho + PE, and Tricho + PH. From an economic point of view, the best treatment for achieving the highest net return was PE. This study underlines that biostimulant features (yield, qualitative aspects, and economic profitability) can be supported through the application of specific biostimulant combinations.